2002
DOI: 10.1007/s00701-002-0975-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Operative Monitoring of Brain Tissue O 2 (PtiO 2 ) During Aneurysm Surgery

Abstract: Intra-operative monitoring of PtiO2 is a complimentary procedure to monitor cerebral perfusion and detect episodes of ischaemia. Given the rapid detection of these events, therapeutic intervention may be initiated before irreversible neuronal damage occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 14 publications
0
15
1
1
Order By: Relevance
“…Over the past decade, brain tissue oxygenation (PbtO 2 ) has been studied in the setting of traumatic brain injury, subarachnoid hemorrhage, and intra-operatively during aneurysm clipping [3][4][5]. The placement of the PbtO 2 probes has been associated with low morbidity, and reliability of data has been confirmed after the first hour of insertion [2,4,5].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Over the past decade, brain tissue oxygenation (PbtO 2 ) has been studied in the setting of traumatic brain injury, subarachnoid hemorrhage, and intra-operatively during aneurysm clipping [3][4][5]. The placement of the PbtO 2 probes has been associated with low morbidity, and reliability of data has been confirmed after the first hour of insertion [2,4,5].…”
Section: Discussionmentioning
confidence: 98%
“…Long-term follow-up has focused largely on the relationship between PbtO 2 and neurologic outcome in adult patients following TBI. These studies have generally demonstrated that decreased brain tissue oxygenation is associated with poor outcome and interventions to increase brain tissue oxygenation improve outcome [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, they also underwent extensive scrutiny leading to identification of several drawbacks and questioning their routine use, particularly in clinical practice. Reported drawbacks included sensor failure (e.g., breakage, cable kinking, probe dislocation, abnormal readings), contamination, infection, hemorrhage, drift, and magnetic resonance imaging (MRI) incompatibility due to the presence of ferromagnetic components [74,[76][77][78][79][80][81][82][83][84][85][86][87][88].…”
Section: Earlier Commercial Solutionsmentioning
confidence: 99%
“…monitoring technology is also used intraoperatively during aneurysm surgery [45,52,[60][61][62][63][64], during surgery of cerebral arterio-venous malformation [60,65,66], functional stereotaxy [67], and during cerebral angiography [68]. It has also been used in patients with spontaneous intraparenchymal hemorrhage [69][70][71][72][73][74][75][76], ischemic stroke in children and adults [36,71,77], severe haemorrhagic stroke [78], and in silent infarcts after subarachnoid hemorrhage [79].…”
Section: Pbto2mentioning
confidence: 99%
“…The second largest group of publications comprises aneurysmal subarachnoid hemorrhage (SAH) [6,7,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Humanmentioning
confidence: 99%